STATISTICAL MODEL OF THE INTENSITY OF THE RAINFALL IN SHUMEN REGION: STATISTICAL MODEL OF THE INTENSITY OF THE RAINFALL IN SHUMEN REGION - Dimanova, Donika; Tsankov, Tsvetoslav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report justifies the view that despite the apparent trend of warming and drought in recent years, there is an increasing frequency of extreme weather and climatic events (rainfall), which cause extensive damage to infrastructure and high costs to the economy and society. Therefore, to improve the performance and effectiveness of State bodies engaged in the prevention or eradication of harmful effects in emergency situations, it is necessary to make scientifically sound estimates of the frequency of intense precipitation over the next few years. Solving this important practical tasks is possible through the development of a statistical model of the intensity of the precipitation.